The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1080/00952990.2020.1771723
|View full text |Cite
|
Sign up to set email alerts
|

Association of E-cigarettes with adolescent alcohol use and binge drinking-drunkenness: A systematic review and meta-analysis

Abstract: Background: E-cigarette (ECIG) use has increased substantially in the past decade. Co-use of alcohol and ECIGS may have serious consequences in adolescents. Objectives: To evaluate the association of e-cigarettes (ECIGs) with alcohol use in adolescents. Methods: Searched databases included PubMed, EMBASE, CINAHL, PsycINFO, Web of Science, and gray literature. Studies were included if they contained a non-E-cigarette group (NON-ECIG), an ECIG group, detailed rates of alcohol use, binge drinking, or drunkenness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 85 publications
2
28
0
Order By: Relevance
“…Three longitudinal studies suggested a temporal relationship in which EC use predates cannabis use [ 55 57 ], suggesting that addressing EC use is an important means of preventing youth cannabis use and of mitigating the adverse neuropsychological effects of cannabis [ 58 , 59 ]. Additionally, another meta-analysis found EC use associated with a six-fold risk of alcohol use and binge drinking in adolescents, though most included studies were cross-sectional and did not sufficiently adjust for confounders [ 60 ].…”
Section: How Does Vaping Relate To Use Of Marijuana and Other Substances?mentioning
confidence: 99%
See 1 more Smart Citation
“…Three longitudinal studies suggested a temporal relationship in which EC use predates cannabis use [ 55 57 ], suggesting that addressing EC use is an important means of preventing youth cannabis use and of mitigating the adverse neuropsychological effects of cannabis [ 58 , 59 ]. Additionally, another meta-analysis found EC use associated with a six-fold risk of alcohol use and binge drinking in adolescents, though most included studies were cross-sectional and did not sufficiently adjust for confounders [ 60 ].…”
Section: How Does Vaping Relate To Use Of Marijuana and Other Substances?mentioning
confidence: 99%
“…Some ECs lead to very high doses of nicotine used, creating stronger addiction risk • Youth who vape are at risk of acute health problems such as EVALI [ 67 ], seizures [ 69 ]. bad oral health [ 70 ], or injury from exploding devices [ 105 , 106 ] • Vaping appears to increase the risk of becoming a CC smoker [ 44 , 46 , 3 , 60 • EC aerosols contain heavy metals, fine particles, and other substances that may be toxic or cancer-causing to vapers and bystanders [ 71 ], so vaping indoors should be avoided • Nicotine and cannabis both affect neurodevelopment and may lead to problems with sleep, concentration, memory, and mental health [ 76 ]. Earlier substance use likely increases these risks [ 51 , 54 ] • Peer influence is important [ 31 ], and adolescents’ perceptions of the importance of peer influence predicts EC use [ 107 ].…”
Section: Counseling Youth and Families About Vapingmentioning
confidence: 99%
“…However, evidence from animal and in-vitro studies show that nicotine, a key component of ENDS, is damaging to the developing brain of children and adolescents. 9 Further, meta-analyses of prospective cohort studies found that use of e-cigarettes in non-smoking children and adolescents might increase the risk of future cigarette smoking 10 and use of other addictive sub stances 3,11,12 ; although at present data are sparse and it remains uncertain whether ENDS or ENNDS use is associated with a gateway effect toward use of tobacco and other substances in children and adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol and nicotine are frequently used sequentially and simultaneously by adolescents 3 with a high prevalence of concurrent e-cigarette vaping and alcohol consumption 4 . Vaping high school students also showed greater alcohol drinking compared to non-vapers 5 , and alcohol and e-cigarette use is the most common type of co-use in this population 6 . The long-term effects of vaping are currently unknown, as are the consequences of e-cigarette/alcohol co-use 6 .…”
Section: Introductionmentioning
confidence: 84%
“…Despite the epidemiological findings indicating frequent associations between e-cigarette use and alcohol consumption 4,5 , there is a scarcity of information regarding the long-term behavioural consequences of their co-use during adolescence. Using a preclinical model of moderate voluntary adolescent alcohol intake and passive nicotine vapour administration, the current study found that exposure to alcohol and vapourized nicotine during this critical developmental period promotes unique sex-specific effects on incentive and associative learning processes.…”
Section: Discussionmentioning
confidence: 99%